VALIDATION OF A TYPOLOGY OF NOVICE TEACHERS’ SUPPORT NEEDS AND COMPARATIVE ANALYSIS BASED ON SOCIODEMOGRAPHIC CHARACTERISTICS - Carpentier, Genevieve; Mukamurera, Joséphine; Leroux, Mylène; Lakhal, Sawsen (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
The first years of teaching are challenging. Knowledge of the kind of support new teachers require is essential. Existing typologies date back from the 1980s and the early 2000s. The aim of this article is twofold: 1) to validate a typology of novice teachers’ support needs using confirmatory factor analysis and 2) to compare these needs in relation to different sociodemographic characteristics (gender, age, employment status, teaching level, and field of study). The quantitative data were drawn from a survey (N = 156) of new teachers. The validated typology highlights five types of support needs. Some key differences emerge from the comparative analyses based on respondents’ age, employment status, and field of study. The results presented could help serve as a framework for better targeting the support to be offered to beginning teachers.